Cost-utility of a specific collaborative group intervention for patients with functional somatic syndromes - Konnopka, Alexander; Kaufmann, Claudia; Wild, Beate; Szecsenyi, Joachim; Herzog, Wolfgang; Schellberg, Dieter; Schäfert, Rainer (Journal of psychosomatic research, 2016)
Collaborative group intervention (CGI) in patients with functional somatic syndromes (FSS) has been shown to improve mental quality of life. To analyse incremental cost-utility of CGI compared to enhanced medical care in patients with FSS. An economic evaluation alongside a cluster-randomised controlled trial was performed. 35 general practitioners (GPs) recruited 300 FSS patients. Patients in the CGI arm were offered 10 group sessions within 3months and 2 booster sessions 6 and 12months after baseline. Costs were assessed via questionnaire. Quality adjusted life years (QALYs) were calculated using the SF-6D index, derived from the 36-item short-form health survey (SF-36). We calculated patients' net-monetary-benefit (NMB), estimated the treatment effect via regression, and generated cost-effectiveness acceptability curves. Using intention-to-treat analysis, total costs during the 12-month study period were 5777EUR in the intervention, and 6858EUR in the control group. Controlling for possible confounders, we found a small, but significant positive intervention effect on QALYs (+0.017; p=0.019) and an insignificant cost saving resulting from a cost-increase in the control group (−10.5%; p=0.278). NMB regression showed that the probability of CGI to be cost-effective was 69% for a willingness to pay (WTP) of 0EUR/QALY, increased to 92% for a WTP of 50,000EUR/QALY and reached the level of 95% at a WTP of 70,375EUR/QALY. Subgroup analyses yielded that CGI was only cost-effective in severe somatic symptom severity (PHQ-15≥15). CGI has a high probability to be a cost-effective treatment for FSS, in particular for patients with severe somatic symptom severity.
Gesehen am 27.11.2017